Effect of feeding ca-salts of fatty acids on fatty acids composition in milk - Sarker, NR; Huque, KS; Islam, H; Das, NG (Bangladesh Journal of Livestock Research, 2016)
A study was undertaken to investigate the effects of Calcium Salt of Fatty Acid on the fatty acids composition of milk fed green German grass and concentrate diet. Twenty lactating Pabna cows having similar daily milk yield (3.4±0.842 Kg) were used and divided into four groups with five animals in each group. The study revealed that saturated fatty acids of milk fat were 61.12, 57.83, 54.93, and 54.56% and unsaturated fatty acids of milk fat were 38.36, 42.22, 45.22 and 45.5 38 % in treatment groups T0 (without Calcium Salt of Fatty Acid), T1 (2.0 % Calcium Salt of Fatty Acid), T2 (2.5 % Calcium Salt of Fatty Acid) and T3 (3.0 % Calcium Salt of Fatty Acid), respectively. The highest unsaturated fatty acid was found in T3 treatment and the lowest in T0 treatment. There is no significant difference between T2 and T3 treatments in relation to unsaturated fatty acids. The palmetic acid content in milk fat were 25.47, 27.22, 26.22 and 26.22% in T0 , T1 , T2 and T3 respectively. The highest palmetic acid found in T2 treatment and the lowest in T0 treatment. The stearic acid content in milk fat were 22.98, 15.78, 13.74 and 13.68% in T0 , T1 , T2 and T3 respectively. The study showed that there is a significant (p<0.01) difference in the treatments for stearic acid content in milk fat. The linoleic acid content in milk fat were 1.57, 1.64, 1.73 and 1.94 % in treatment groups T0 , T1 , T2 and T3 respectively. It may be concluded that the feeding Ca-Salts of Fatty Acids increased unsaturation of milk fat, oleic acid, linoleic acid and linolenic acid and decrease saturation and stearic acid content in milk fat. Bangladesh J. of Livestock Res. 19(1-2): 10-17, Jan-Dec 2012